The relationship between metacognitive skills, learned helplessness, and aboriginal students performance in LINUS - Abdul Rahman Shafie, Shazreen; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The overall goal of this study is to observe the relationship between metacognitive skills, learned helplessness and aboriginal performance in LINUS. A correlational design will be adopted to answer the research questions of this study. Two types of questionnaires will be given which are Jr. MAI Inventory and Learned Helplessness Scale in order to achieve the objectives. Purposive sampling technique will be employed to recruit participants. Sample of the population will be taken among the year 2, 3, 4 and 5. Upon completion of data analyses, it is expected that there is a positive relationship between metacognitive skills and LINUS performance among aboriginal school children. Lacking in metacognitive components will indicate poor learning performance among the children. Is is expected that there is also a relationship between learned helplessness and LINUS performance in which aboriginal school children have higher levels of learned helplessness and it is related to the low performance in LINUS.